AR splice variants in circulating tumor cells of patients with castration‐resistant prostate cancer: relation with outcome to cabazitaxel - Anieta M. Sieuwerts; Wendy Onstenk; Jaco Kraan; Corine M. Beaufort; Mai Van; Bram De Laere; Luc Y. Dirix; Paul Hamberg; Aart Beeker; Hielke J. Meulenbeld; Geert‐Jan Creemers; Wytske M. vanWeerden; et al. (Molecular Oncology, 2019)
The androgen receptor splice variant (AR‐V) 7 in circulating tumor cells (CTCs) is a predictor for resistance to anti‐AR‐targeted treatment, but not to taxane‐based chemotherapy in metastatic castration‐resistant prostate cancer (mCRPC). In this study, we investigated whether the presence of two constitutively active variants (AR‐V3, AR‐V7) and two other conditionally activated variants (AR‐V1, AR‐V9) vs full‐length androgen receptor (AR‐FL) measured in CTCs from patients with mCRPC were associated with outcome to therapy with the taxane cabazitaxel. Blood was collected at baseline and after two cycles of cabazitaxel from 118 mCRPC patients starting cabazitaxel in a prospective phase II trial. CellSearch‐enriched CTCs were enumerated and in parallel characterized for the presence of the AR‐Vs by reverse transcription quantitative polymerase chain reaction. Correlations with CTC and prostate‐specific antigen response to cabazitaxel as well as associations with overall survival (OS) were investigated. All AR‐Vs were frequently present and co‐expressed at frequencies of 31–48% at baseline and at 19–40% after two cycles of cabazitaxel. No specific directions of change in the measured variants were detected between the start of treatment and after two cycles of cabazitaxel. No associations between the presence of AR‐V3 and AR‐V7 and outcome to cabazitaxel were observed. While a reduction in CTCs to < 5 CTCs during treatment (CTC5‐response) was less often observed in patients with AR‐V9‐positive CTCs at baseline (P = 0.004), the CTC5‐adjusted detection of AR‐V1 after two cycles of cabazitaxel was an independent prognostic factor for OS [HR 2.4 (95% CI 1.1–5.1, P = 0.03)]. These novel findings are expected to contribute to more personalized treatment approaches in mCRPC patients.